1997
DOI: 10.3171/jns.1997.86.4.0603
|View full text |Cite
|
Sign up to set email alerts
|

Intracarotid infusion of RMP-7, a bradykinin analog, and transport of gallium-68 ethylenediamine tetraacetic acid into human gliomas

Abstract: The bradykinin analog, RMP-7, was investigated for its ability to increase selectively the transport of 68Ga ethylenediamine tetraacetic acid (EDTA) into recurrent malignant gliomas in nine patients. For each patient, two position emission tomography (PET) studies (one with and one without RMP-7) were performed. For studies with RMP-7, 10 to 300 ng/kg of the compound was infused into the supraophthalmic carotid artery over 15 minutes. In each PET study, a sequence of PET scans was initiated simultaneously with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…13,22,23 In one study in humans, intra-arterial RMP-7 increased the transport of a small molecular weight PET tracer by 46 ± 42% into gliomas; and similar to our findings, the normal brain tissue was not significantly affected. 24 In addition to CNS effects, RMP-7 also had peripheral effects on viral distribution. Bradykinin, when infused intravenously has been shown to increase vascular resistance to the splanchnic bed and visceral organs (liver, stomach, small and large intestine, pancreas and mesentery).…”
Section: Discussionmentioning
confidence: 99%
“…13,22,23 In one study in humans, intra-arterial RMP-7 increased the transport of a small molecular weight PET tracer by 46 ± 42% into gliomas; and similar to our findings, the normal brain tissue was not significantly affected. 24 In addition to CNS effects, RMP-7 also had peripheral effects on viral distribution. Bradykinin, when infused intravenously has been shown to increase vascular resistance to the splanchnic bed and visceral organs (liver, stomach, small and large intestine, pancreas and mesentery).…”
Section: Discussionmentioning
confidence: 99%
“…RMP-7 has been used previously to enhance the delivery of chemotherapeutic agents to brain tumors and is approved for human use. 28,29 This is the first report of the use of intracarotid RMP-7 infusion to enhance the intra-arterial delivery of HSV vectors to experimental brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of Cereport's selectivity to tumour vasculature has been confirmed in the clinic using imaging techniques in glioma patients (Ford et al, 1996;Black et al, 1997). These preliminary clinical studies in human recurrent gliomas have also suggested that Cereport combined with carboplatin provides increased patient benefit when compared to carboplatin alone (Prados et al, 1997) or standard care (Gregor et al, 1997).…”
Section: Discussionmentioning
confidence: 75%
“…Testing in animal models of glioma Elliott et al, 1996aElliott et al, , 1996bElliott et al, , 1996cMatsukado et al, 1996Matsukado et al, , 1998, as well as imaging studies in glioma patients (Warkne et al, 1995;Ford et al, 1996;Black et al, 1997) have demonstrated that Cereport not only increases permeability of the vasculature supplying brain tumours, but does so selectively. That is, the increased permeability is approximately 10-20 times greater in brain areas associated with tumours, as compared to normal, nontumour brain .…”
mentioning
confidence: 99%